Research progress in the clinical application of minimally invasive orthognathic surgery - WANG Ruiyang; LIU Kai; WANG Xudong (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Orthognathic surgery is a procedure that involves cutting the deformed segments of the upper and lower jawbones and moving the dentoalveolar complex to a predetermined corrective position, aiming to establish a harmonious dental arch and occlusal relationship and improve facial appearance. With the rapid advancement of medical technology and the accumulation of clinical experience, minimally invasive orthognathic surgery, which uses endoscopy, piezoelectric bone scalpels, lasers, navigation systems, and robotic-assisted surgical devices, is gaining increasing attention due to its advantages of minimal trauma and high precision. However, the clinical application of minimally invasive orthognathic surgery has not yet been systematically explored. Given its significant role in advancing the field of orthognathic surgery, this paper aims to provide a comprehensive review of the latest progress in the clinical application of minimally invasive orthognathic surgery and offer an outlook on future directions, with the goal of providing valuable insights for future research and clinical practice.